A decade in banking Ewing sarcoma: a report from the children’s oncology group - Borinstein, Scott C.; Beeler, Natalie; Block, John; Gorlick, Richard; Grohar, Patrick; Jedlicka, Paul; Krailo, Mark; Morris, Carol; Phillips, Sharon; Siegal, Gene P.; Lawlor, Elizabeth; Lessnick, Stephen (Frontiers in Oncology, 2013)
Outcomes for patients with metastatic and recurrent Ewing sarcoma remain poor and a better understanding of the biology of this malignancy is critical to the development of prognostic biomarkers and novel therapies. Therefore, the Children’s Oncology Group (COG) has created tissue banking protocols designed to collect high quality clinically annotated tumor specimens that can be distributed to researchers to perform basic science and correlative investigation. Data from the COG Ewing sarcoma tissue banking protocols AEWS02B1 and its successor study AEWS07B1 were reviewed in this study. 635 patients were enrolled on AEWS02B1 and 396 patients have had tissue submitted to AEWS07B1. The average age of participation was 13.2 years. 86% were less than 19 years old and only 6% were greater than 21 years of age at diagnosis. When compared to SEER data, approximately 18% of all cases and only 8% of all patients >20 years old diagnosed with Ewing sarcoma annually in the United States have had tumor banked. The majority of participants submitted formalin fixed paraffin embedded primary tumor and blood samples. In total, fresh frozen tissue was submitted for only 29% of cases. Only 7 metastatic tumor samples have been collected. Although the COG has been successful in collecting tumor samples from patients newly diagnosed with Ewing sarcoma, fresh frozen tumor specimens from primary and metastatic disease are critically needed, especially from young adult patients, in order to conduct high quality basic science and translational research investigation with a goal of developing better treatments.